Green superfine high-performance composite admixture as well as preparation method and application thereof

By using green ultrafine high-performance composite blends, the microstructure and hydration degree of concrete are improved, and cracks are repaired by using Bacillus basophilus, the problems of poor durability and structural cracking of high-performance concrete are solved, and the strength and durability are improved significantly, and the characteristics of self-healing are provided.

CN119591346AActive Publication Date: 2025-03-11LIANGSHAN SAIDI BUILDING MATERIALS TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411676898.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-11
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

The existing high-performance concrete has poor durability, is prone to structural cracking problems, and the existing repair methods are not effective.

Method used

Green ultrafine high-performance composite admixtures are used, including fly ash, microsilicon powder, mesoporous silica, nano calcium carbonate, basophilic Bacillus agent, etc., fly ash is activated and compound grinding is formed by silane coupling agent to form fine pores and high specific surface area, improve the microstructure and hydration of concrete, and repair cracks by basophilic Bacillus.

Benefits of technology

It significantly improves the strength and durability of concrete, improves crack resistance and ion corrosion resistance, has self-repair characteristics, and can effectively extend the service life of concrete under harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591346A_ABST
    Figure CN119591346A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of high-performance concrete, and particularly discloses a green superfine high-performance composite admixture as well as a preparation method and application thereof. The green superfine high-performance composite admixture is prepared from the following raw materials: fly ash, silica fume, a silane coupling agent, mesoporous silica, waste building materials, nano calcium carbonate, nano bentonite, polyethylene wax, paraffin, fatty glyceride, calcium lactate, acrylamide, ammonium persulfate, a bacillus alcalophilus agent, limestone powder, urea, a light calcined magnesia expanding agent and quartz powder. Redispersible latex powder and a defoaming agent. The invention is green and environment-friendly, effectively saves the cost input, has the characteristic of self-repairing, can be applied to concrete engineering in harsh environment, and effectively improves the long-term durability of high-performance concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete admixtures, and in particular to a green ultra-fine high-performance composite admixture and a preparation method and application thereof. Background Art

[0002] Cement concrete has the engineering properties of easy availability, versatility, adaptability, relative economy and the ability to be applied to a variety of structural types, and has become the most commonly used structural material in the world. As the most widely used building material in engineering construction, with the development of engineering construction and science and technology, concrete structures have become diversified, and high strength and high performance of concrete have become people's pursuit.

[0003] At present, the working environment of cement concrete is becoming more and more harsh, and the requirements for its early and long-term durability are also getting higher and higher. Compared with ordinary concrete, high-performance concrete has superior characteristics such as high durability, high workability, and high volume stability. It can use various industrial waste slag and minerals, reduce pollution to the natural environment and energy consumption, and is easy to construct and reduce labor input. It is the development trend of green concrete in the future.

[0004] The degradation process of cement-based materials is the process in which the original micro-defects of concrete continue to expand and form macro-cracks under the influence of external factors; and the penetration of various micro-cracks in concrete provides a fast channel for the invasion of harmful media, which seriously affects the durability and service life of concrete structures. At present, due to the insufficient stability of cement hydrates in concrete, high-performance concrete has poor durability.

[0005] Nowadays, the microstructure of cement-based materials can be improved by adding ultra-fine admixtures, the hydration degree of cement-based materials can be increased, and the service life of reinforced concrete structures can be extended. However, reinforced concrete is prone to fine cracks due to structural stress, leading to structural cracking problems. Currently, concrete cracks are usually repaired manually, but the effect of repairing cracks is not ideal. Summary of the invention

[0006] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a green ultra-fine high-performance composite admixture and a preparation method and application thereof.

[0007] A green ultrafine high-performance composite admixture, the raw materials of which include, by mass, 20-50 parts of fly ash, 15-25 parts of microsilica powder, 1.1-3 parts of silane coupling agent, 5-10 parts of mesoporous silica, 5-10 parts of waste building materials, 1-5 parts of nano calcium carbonate, 1-2 parts of nano bentonite, 1-3 parts of polyethylene wax, 10-20 parts of paraffin wax, 1-2 parts of fatty acid glyceride, 1-3 parts of calcium lactate, 1-4 parts of acrylamide, 0.01-0.1 parts of ammonium persulfate, 1-2 parts of alkaliphilic bacillus agent, 15-30 parts of limestone powder, 5-10 parts of urea, 1-6 parts of light-burned magnesium oxide expansion agent, 3-15 parts of quartz powder, 0.1-2 parts of redispersible latex powder and 0.1-0.5 parts of defoaming agent.

[0008] Preferably, the density of microsilica powder is ≥550kg / m 3 , of which SiO2 and Al2O3 account for ≥95% by mass.

[0009] Preferably, the particle size of the mesoporous silica is 100-500 nm.

[0010] Preferably, the silane coupling agent is at least one of silane coupling agent KH570, silane coupling agent KH590, and silane coupling agent Si69.

[0011] Preferably, the redispersible latex powder is redispersible vinyl acetate / ethylene copolymer rubber powder.

[0012] Preferably, the alkaliphilic Bacillus agent contains 1-5×10 9 cfu / g.

[0013] Preferably, the alkaliphilic Bacillus is at least one of Bacillus sphaericus, Bacillus pasteurianus, Bacillus cohnii, Bacillus cereus and Bacillus licheniformis.

[0014] The preparation method of the green ultrafine high-performance composite admixture comprises the following steps:

[0015] S1. Mix fly ash and microsilica powder uniformly to obtain premix a;

[0016] S2, grind the silane coupling agent, mesoporous silica and waste building materials for 10-20 min, add nano calcium carbonate, nano bentonite and polyethylene wax and continue grinding for 5-15 min, add paraffin, fatty acid glyceride and calcium lactate, stir at 70-80° C. to obtain premix b;

[0017] S3, grind the silane coupling agent and fly ash, add deionized water and acrylamide, stir for 1-2h, add ammonium persulfate, stir at 70-80°C for 1-2h, cool to room temperature, add alkaliphilic bacillus agent, ultrasonically disperse for 1-4h, centrifuge, freeze-dry, crush and sieve, send into a drum, spray premix b on the surface, and freeze-dry to obtain premix c;

[0018] S4. Mix limestone powder, urea, light-burned magnesium oxide expansion agent, quartz powder, redispersible latex powder and defoaming agent evenly, add premix a and premix c thereto and mix evenly.

[0019] Preferably, the mass ratio of the silane coupling agent used in S2 to the silane coupling agent used in S3 is 0.1-1:1-2.

[0020] Preferably, in S2, the mesh size of the material after adding nano calcium carbonate, nano bentonite and polyethylene wax and grinding is 700-1000 mesh.

[0021] Preferably, in S3, the ultrasonic frequency is 5-12 kHz.

[0022] The application of the above green ultrafine high-performance composite admixture in the preparation of concrete.

[0023] The green ultrafine high-performance composite admixture can replace 3-15% of the cement mass in concrete.

[0024] Beneficial effects:

[0025] The present invention adopts silane coupling agent, mesoporous silica and waste building materials for compound activation, and has good compatibility and lubricity with nano calcium carbonate and nano bentonite in combination with polyethylene wax, and can be evenly dispersed in paraffin; the fly ash is then activated by the silane coupling agent, and then grafted with polyacrylamide, so as to significantly enhance the adsorption and load strength of the fly ash on alkaliphilic bacillus, further coat the premix b, and the product is dispersed among the admixtures, which can not only effectively reduce the surface energy between particles and effectively reduce the agglomeration of particles, but also absorb water and expand after the wall is broken, can closely fit the cracks to achieve filling and plugging, react with water, calcium hydroxide and other substances at the crack interface to repair the cracks, and at the same time, the alkaliphilic bacillus further overflows after the wall is broken, and the cracks are further repaired, so as to comprehensively improve the strength and durability of concrete, and the repair effect is excellent.

[0026] The present invention adopts mesoporous silica and waste building materials for compound grinding, which not only forms a large number of fine pores and a large specific surface area, but also the high silica content can effectively promote the formation of hydration products and effectively improve the void structure of concrete materials; and the combination of fly ash and microsilica powder has good porosity, and is combined with prefabricated material c to have extremely good dispersion uniformity in the admixture, which not only effectively promotes the dispersion of structural stress, thereby producing an effective strengthening effect, but also can inhibit the generation and development of fine cracks, and has a significant structural stress compensation and anti-cracking effect.

[0027] The present invention is not only green and environmentally friendly, but also effectively saves cost investment. It can also alleviate the problem of tight supply of traditional mineral admixtures, reduce engineering costs, enhance internal maintenance, and reduce cracking problems caused by stress in high-performance concrete structures. The concrete has good fluidity, water retention, and workability, and has extremely high density and uniformity. It has excellent crack resistance and resistance to ion corrosion, good volume stability, and self-repairing characteristics. It can be applied to concrete projects in harsh environments, and effectively improve the long-term durability of high-performance concrete. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a comparison chart of the flexural strength of concrete samples of Example 5 and Comparative Examples 1-3.

[0029] Figure 2 This is a comparison chart of the compressive strength of concrete samples of Example 5 and Comparative Examples 1-3 after standard curing for different times.

[0030] Figure 3 It is a comparison chart of the early compressive strength ratio of the concrete specimens of Example 5 and Comparative Examples 1-3.

[0031] Figure 4 It is a comparison chart of the strength loss rate of concrete samples of Example 5 and Comparative Examples 1-3 after 200 freeze-thaw cycles.

[0032] Figure 5 It is the self-repair rate curve of the concrete samples of Example 5 and Comparative Examples 1-2. DETAILED DESCRIPTION

[0033] The present invention will be further explained below in conjunction with specific embodiments.

[0034] The fly ash used in the following is a new type of ultra-fine volcanic ash powder micro-beads produced by Beijing Mouyuan Yixinxin Material Technology Co., Ltd. The microsilica powder used in the following is purchased from Shijiazhuang Moujiang Mineral Products Co., Ltd. After random inspection, its density is 557.29kg / m 3, the mass percentage of SiO2 and Al2O3 is 95.26%. The mesoporous silica used below was purchased from Qinghe County Moujiang Metal Materials Co., Ltd., and its average particle size was 200nm after random inspection. The waste building materials used below were purchased from Zhengzhou Yuanmoufa Environmental Protection Technology Co., Ltd., and its screening results were shown in Table 1 after random inspection:

[0035] Table 1 Screening results of waste building materials

[0036]

[0037] The light-burned magnesium oxide expansion agent used below was purchased from a certain Xu magnesium material factory in Yingkou Nanlou Economic Development Zone, with a particle size of 250 mesh. The redispersible latex powder used below (anti-saponification redispersible vinyl acetate / ethylene copolymer powder) is from Wacker Chemie. Hebei Xing Chemical Co., Ltd., item number 5134. The polyether-modified silicone defoamer used below was purchased from Qingdao Sidi Silicone Co., Ltd., model number MSD-916.

[0038] The strain deposit number of the Bacillus sphaericus used below is CCTCC WB 20081587; the strain deposit number of the Bacillus cohnii used below is CCTCC WB 20081136; the strain deposit number of the Bacillus cereus used below is CCTCC AB 93038. All three are from the China Center for Type Culture Collection.

[0039] Example 1

[0040] A green ultrafine high-performance composite admixture, the raw materials of which include: 200g fly ash, 150g microsilica, 1g silane coupling agent KH570, 10g silane coupling agent Si69, 50g mesoporous silica, 50g waste building materials, 10g nano calcium carbonate, 10g nano bentonite, 10g polyethylene wax, 100g paraffin, 10g fatty acid glyceride, 10g calcium lactate, 10g acrylamide, 0.1g ammonium persulfate, and a live bacteria content of 1×10 9 10g of spherical Bacillus agent with a cfu / g content, 150g of limestone powder, 50g of urea, 10g of light-burned magnesium oxide expansion agent, 30g of quartz powder, 1g of redispersible latex powder, and 1g of polyether-modified silicone defoaming agent.

[0041] The preparation method of the green ultrafine high-performance composite admixture comprises the following steps:

[0042] S1. 100g of fly ash and microsilica powder were mixed evenly to obtain premix a. The specific surface area of ​​premix a was 812m 2 / kg;

[0043] S2, silane coupling agent KH570, mesoporous silica, and waste building materials were mixed and ground for 10 minutes at a grinding speed of 1000 r / min, and nano calcium carbonate, nano bentonite, and polyethylene wax were added thereto and continued to grind for 5 minutes, and after passing through a 700-mesh sieve without sieve residue, paraffin, fatty acid glyceride, and calcium lactate were added, and stirred evenly at a temperature of 70° C. to obtain a premix b;

[0044] S3, silane coupling agent Si69 and 100g fly ash are mixed and ground at a grinding speed of 1000r / min, 400g deionized water and acrylamide are added and stirred for 1h, ammonium persulfate is added, stirred at a temperature of 70°C for 1h, cooled to room temperature, spherical Bacillus agent is added and ultrasonically dispersed for 1h, the ultrasonic frequency is 5kHz, centrifuged, freeze-dried, crushed through a 50-mesh sieve, sent into a drum, premix b is sprayed on the surface, and freeze-dried to obtain premix c;

[0045] S4. Mix limestone powder, urea, light-burned magnesium oxide expansion agent, quartz powder, redispersible latex powder, and polyether-modified silicone defoaming agent evenly, and add premix a and premix c thereto and mix evenly.

[0046] Example 2

[0047] A green ultrafine high-performance composite admixture, the raw materials of which include: 500g fly ash, 250g microsilica, 10g silane coupling agent KH590, 20g silane coupling agent KH570, 100g mesoporous silica, 100g waste building materials, 50g nano calcium carbonate, 20g nano bentonite, 30g polyethylene wax, 200g paraffin, 20g fatty acid glyceride, 30g calcium lactate, 40g acrylamide, 1g ammonium persulfate, and the content of live bacteria is 5×10 9 20g of Bacillus cohnii agent with a cfu / g content, 300g of limestone powder, 100g of urea, 60g of light-burned magnesium oxide expansion agent, 150g of quartz powder, 20g of redispersible latex powder, and 5g of polyether-modified silicone defoaming agent.

[0048] The preparation method of the green ultrafine high-performance composite admixture comprises the following steps:

[0049] S1. 300 g of fly ash and microsilica powder were mixed evenly to obtain premix a. The specific surface area of ​​premix a was 1076 m 2 / kg;

[0050] S2, silane coupling agent KH590, mesoporous silica, and waste building materials were mixed and ground for 20 minutes at a grinding speed of 2000 r / min, and nano calcium carbonate, nano bentonite, and polyethylene wax were added thereto and continued to grind for 15 minutes, and after passing through a 1000 mesh sieve without sieve residue, paraffin, fatty acid glyceride, and calcium lactate were added, and stirred evenly at a temperature of 80° C. to obtain a premix b;

[0051] S3, silane coupling agent KH570 and 200g fly ash are mixed and ground at a grinding speed of 2000r / min, 600g deionized water and acrylamide are added and stirred for 2h, ammonium persulfate is added, stirred at a temperature of 80°C for 2h, cooled to room temperature, Bacillus cohnii agent is added and ultrasonically dispersed for 4h at an ultrasonic frequency of 12kHz, centrifuged, freeze-dried, crushed through an 80-mesh sieve, sent into a drum, premix b is sprayed on the surface, and freeze-dried to obtain premix c;

[0052] S4. Mix limestone powder, urea, light-burned magnesium oxide expansion agent, quartz powder, redispersible latex powder, and polyether-modified silicone defoaming agent evenly, and add premix a and premix c thereto and mix evenly.

[0053] Example 3

[0054] A green ultrafine high-performance composite admixture, the raw materials of which include: 430g fly ash, 180g microsilica powder, 20g silane coupling agent KH570, 90g mesoporous silica, 70g waste building materials, 40g nano calcium carbonate, 13g nano bentonite, 25g polyethylene wax, 120g paraffin, 18g fatty acid glyceride, 15g calcium lactate, 30g acrylamide, 0.3g ammonium persulfate, and a live bacteria content of 4×10 9 13g cfu / g Bacillus cereus agent, 240g limestone powder, 70g urea, 50g light-burned magnesium oxide expansion agent, 70g quartz powder, 14g redispersible latex powder, and 2g polyether modified silicone defoaming agent.

[0055] The preparation method of the green ultrafine high-performance composite admixture comprises the following steps:

[0056] S1. 250 g of fly ash and microsilica powder were mixed evenly to obtain premix a. The specific surface area of ​​premix a was 893 m 2 / kg;

[0057] S2, 7g of silane coupling agent KH570, mesoporous silica, and waste building materials were mixed and ground for 12min at a grinding speed of 1700r / min, and nano calcium carbonate, nano bentonite, and polyethylene wax were added thereto and continued to grind for 8min, and after passing through an 800-mesh sieve without sieve residue, paraffin, fatty acid glyceride, and calcium lactate were added, and stirred evenly at a temperature of 77°C to obtain a premix b;

[0058] S3, 13g of silane coupling agent KH570 and 180g of fly ash were mixed and ground at a grinding speed of 1200r / min, 550g of deionized water and acrylamide were added and stirred for 80min, ammonium persulfate was added, and the mixture was stirred at 77°C for 80min, cooled to room temperature, and Bacillus cereus agent was added and ultrasonically dispersed for 3h at an ultrasonic frequency of 6kHz, centrifuged, freeze-dried, crushed through a 70-mesh sieve, and fed into a drum, premix b was sprayed on the surface, and premix c was obtained by freeze-drying;

[0059] S4. Mix limestone powder, urea, light-burned magnesium oxide expansion agent, quartz powder, redispersible latex powder, and polyether-modified silicone defoaming agent evenly, and add premix a and premix c thereto and mix evenly.

[0060] Example 4

[0061] A green ultrafine high-performance composite admixture, the raw materials of which include: 270g fly ash, 220g microsilica powder, 20g silane coupling agent KH570, 70g mesoporous silica, 90g waste building materials, 20g nano calcium carbonate, 17g nano bentonite, 15g polyethylene wax, 180g paraffin, 12g fatty acid glyceride, 25g calcium lactate, 20g acrylamide, 0.7g ammonium persulfate, and a live bacteria content of 2×10 9 17g of Bacillus cereus agent with a cfu / g content, 200g of limestone powder, 90g of urea, 20g of light-burned magnesium oxide expansion agent, 110g of quartz powder, 7g of redispersible latex powder, and 4g of polyether-modified silicone defoaming agent.

[0062] The preparation method of the green ultrafine high-performance composite admixture comprises the following steps:

[0063] S1. 150 g of fly ash and microsilica powder were mixed evenly to obtain premix a. The specific surface area of ​​premix a was 969 m 2 / kg;

[0064] S2, 3g of silane coupling agent KH570, mesoporous silica, and waste building materials were mixed and ground for 18min at a grinding speed of 1300r / min, and nano calcium carbonate, nano bentonite, and polyethylene wax were added thereto and continued to grind for 12min, and after passing through a 900-mesh sieve without sieve residue, paraffin, fatty acid glyceride, and calcium lactate were added, and stirred evenly at a temperature of 73°C to obtain a premix b;

[0065] S3, 17g of silane coupling agent KH570 and 120g of fly ash were mixed and ground at a grinding speed of 1800r / min, 450g of deionized water and acrylamide were added and stirred for 100min, ammonium persulfate was added, stirred at a temperature of 73°C for 100min, cooled to room temperature, Bacillus cereus agent was added and ultrasonically dispersed for 2h at an ultrasonic frequency of 9kHz, centrifuged, freeze-dried, crushed through a 60-mesh sieve, sent into a drum, premix b was sprayed on the surface, and freeze-dried to obtain premix c;

[0066] S4. Mix limestone powder, urea, light-burned magnesium oxide expansion agent, quartz powder, redispersible latex powder, and polyether-modified silicone defoaming agent evenly, and add premix a and premix c thereto and mix evenly.

[0067] Example 5

[0068] A green ultrafine high-performance composite admixture, the raw materials of which include: 350g fly ash, 200g microsilica powder, 20g silane coupling agent KH570, 80g mesoporous silica, 80g waste building materials, 30g nano calcium carbonate, 15g nano bentonite, 20g polyethylene wax, 150g paraffin, 15g fatty acid glyceride, 20g calcium lactate, 25g acrylamide, 0.5g ammonium persulfate, and a live bacteria content of 3×10 9 15g cfu / g Bacillus cereus agent, 220g limestone powder, 80g urea, 35g light-burned magnesium oxide expansion agent, 90g quartz powder, 10g redispersible latex powder, and 3g polyether modified silicone defoaming agent.

[0069] The preparation method of the green ultrafine high-performance composite admixture comprises the following steps:

[0070] S1. 200g of fly ash and microsilica powder were mixed evenly to obtain premix a. The specific surface area of ​​premix a was 943m 2 / kg;

[0071] S2, 5g of silane coupling agent KH570, mesoporous silica, and waste building materials were mixed and ground for 15min at a grinding speed of 1500r / min, and nano calcium carbonate, nano bentonite, and polyethylene wax were added thereto and continued to grind for 10min, and after passing through an 800-mesh sieve without sieve residue, paraffin, fatty acid glyceride, and calcium lactate were added, and stirred evenly at a temperature of 75°C to obtain a premix b;

[0072] S3, 15g of silane coupling agent KH570 and 150g of fly ash were mixed and ground at a grinding speed of 1500r / min, 500g of deionized water and acrylamide were added and stirred for 90min, ammonium persulfate was added, and the mixture was stirred at 75°C for 90min, cooled to room temperature, and Bacillus cereus agent was added and ultrasonically dispersed for 2.5h at an ultrasonic frequency of 7.5kHz, centrifuged, freeze-dried, crushed through a 65-mesh sieve, and fed into a drum, premix b was sprayed on the surface, and freeze-dried to obtain premix c;

[0073] S4. Mix limestone powder, urea, light-burned magnesium oxide expansion agent, quartz powder, redispersible latex powder, and polyether-modified silicone defoaming agent evenly, and add premix a and premix c thereto and mix evenly.

[0074] Comparative Example 1

[0075] A green ultrafine high-performance composite admixture, the raw materials of which include: 350g fly ash, 200g microsilica powder, 20g silane coupling agent KH570, 80g mesoporous silica, 80g waste building materials, 30g nano calcium carbonate, 15g nano bentonite, 20g polyethylene wax, 150g paraffin, 15g fatty acid glyceride, 20g calcium lactate, and a live bacteria content of 3×10 9 15g cfu / g Bacillus cereus agent, 220g limestone powder, 80g urea, 35g light-burned magnesium oxide expansion agent, 90g quartz powder, 10g redispersible latex powder, and 3g polyether modified silicone defoaming agent.

[0076] The preparation method of the green ultrafine high-performance composite admixture comprises the following steps:

[0077] S1. Mix 200g of fly ash and microsilica powder to form premix a. The specific surface area of ​​premix a is 943m 2 / kg;

[0078] S2, 5g of silane coupling agent KH570, mesoporous silica, and waste building materials were mixed and ground for 15min at a grinding speed of 1500r / min, and nano calcium carbonate, nano bentonite, and polyethylene wax were added thereto and continued to grind for 10min, and after passing through an 800-mesh sieve without sieve residue, paraffin, fatty acid glyceride, and calcium lactate were added, and stirred evenly at a temperature of 75°C to obtain a premix b;

[0079] S3, 15g of silane coupling agent KH570 and 150g of fly ash were mixed and ground at a grinding speed of 1500r / min, 500g of deionized water and Bacillus cereus agent were added, ultrasonic dispersion was performed for 2.5h, the ultrasonic frequency was 7.5kHz, centrifuged, freeze-dried, crushed through a 65-mesh sieve, sent into a drum, premix b was sprayed on the surface, and freeze-dried to obtain premix c;

[0080] S4. Mix limestone powder, urea, light-burned magnesium oxide expansion agent, quartz powder, redispersible latex powder, and polyether-modified silicone defoaming agent evenly, and add premix a and premix c thereto and mix evenly.

[0081] Comparative Example 2

[0082] A green ultrafine high-performance composite admixture, the raw materials of which include: 350g fly ash, 200g microsilica powder, 20g silane coupling agent KH570, 80g mesoporous silica, 80g waste building materials, 30g nano calcium carbonate, 15g nano bentonite, 20g polyethylene wax, 150g paraffin, 15g fatty acid glyceride, 20g calcium lactate, 25g acrylamide, 0.5g ammonium persulfate, and a live bacteria content of 3×10 9 15g cfu / g Bacillus cereus agent, 220g limestone powder, 80g urea, 35g light-burned magnesium oxide expansion agent, 90g quartz powder, 10g redispersible latex powder, and 3g polyether modified silicone defoaming agent.

[0083] The preparation method of the green ultrafine high-performance composite admixture comprises the following steps:

[0084] S1. 200g of fly ash and microsilica powder were mixed evenly to obtain premix a. The specific surface area of ​​premix a was 943m 2 / kg;

[0085] S2, 5g of silane coupling agent KH570, mesoporous silica, and waste building materials were mixed and ground for 15min at a grinding speed of 1500r / min, and nano calcium carbonate, nano bentonite, and polyethylene wax were added thereto and continued to grind for 10min, and there was no residue after passing through an 800-mesh sieve, and paraffin, fatty acid glyceride, and calcium lactate were added, and stirred evenly at a temperature of 75°C, cooled to room temperature, crushed, and then 15g of silane coupling agent KH570, 150g of fly ash, acrylamide, ammonium persulfate, and Bacillus cereus agent were added and mixed evenly to obtain a premix c;

[0086] S3, limestone powder, urea, light-burned magnesium oxide expansion agent, quartz powder, redispersible latex powder, polyether-modified silicone defoaming agent are mixed evenly, and premix a and premix c are added thereto and mixed evenly.

[0087] Comparative Example 3

[0088] A green ultrafine high-performance composite admixture, whose raw materials include: 350g of fly ash, 200g of microsilica powder, 80g of waste building materials, 10g of redispersible latex powder, and 3g of polyether modified silicone defoamer.

[0089] The preparation method of the green ultrafine high-performance composite admixture comprises the following steps: uniformly mixing fly ash, microsilica powder, waste building materials, redispersible latex powder and polyether modified silicone defoaming agent.

[0090] The green ultrafine high-performance composite admixtures obtained in Example 5 and Comparative Examples 1-3 were added to molded concrete, and the performance after curing was compared, as shown in detail below:

[0091] The raw materials of each group are: PO 52.5 Portland cement 780kg / m 3 , green ultra-fine high-performance composite admixture 120kg / m 3 , 5-31.5mm crushed stone 125kg / m 3 , fine aggregate (mechanical sand) 950kg / m 3 , water 200kg / m 3 , polycarboxylate water reducer 25kg / m 3 .

[0092] Each group mixes the corresponding raw materials according to the ratio and pours them out immediately after 120s. Referring to GB / T17671-2021 "Test method for strength of cement mortar (ISO method)", each group of mortar is poured into 40mm×40mm×160mm specification specimens and cured for the corresponding standard time.

[0093] After the curing is completed, the flexural strength test is carried out first, and the compression test is carried out on the broken prism. The compression surface is the two side surfaces of the specimen when it is formed, with an area of ​​40mm×40mm.

[0094] The flexural strength is tested on a compression-flexure testing machine. The side of the specimen is placed on the fixture, and the loading rate of the testing machine is 50±10N / s. Then the side of the broken specimen end is placed on the fixture, and the loading rate is set to 2400±200N / s, and the loading is uniformly applied until the specimen is destroyed.

[0095] like Figure 1 As shown, after 28 days of curing, the flexural strength of the Example 5 group was the highest, which was better than that of the other groups (P < 0.05).

[0096] like Figure 2 As shown, the compressive strength of Example 5 group after curing for different time periods was always higher than that of the other groups (P < 0.05), but it was difficult to evaluate the early strength of each group. The applicant compared the 3d compressive strength and 7d compressive strength with the 28d compressive strength, and calculated the percentage of the early compressive strength of each group to the final compressive strength.

[0097] like Figure 3As shown, the early compressive strength ratio of the Example 5 group is always higher than that of the other groups (P < 0.05), which proves that the green ultrafine high-performance composite admixture obtained in Example 5 can effectively improve the early strength of concrete.

[0098] The permeability grade of each group of samples after 28 days of standard curing was tested with reference to GB50164-2011 "Concrete Quality Control Standard". The permeability grade of the samples in Example 5 reached P27, the permeability grade of the samples in Comparative Example 1 was P18, the permeability grade of the samples in Comparative Example 2 was P22, and the permeability grade of the samples in Comparative Example 3 was P14.

[0099] After standard curing for 28 days, each group of specimens is immersed in 20±2℃ water for 4 days, and the immersion water level is 25.0±5.0mm higher than the top surface of the specimen. After the immersion, take out the specimens and wipe off the moisture on the surface of the specimens, and measure and weigh the appearance dimensions. Each specimen is placed in a specimen box and then in a freeze-thaw chamber, with a 20mm gap between the specimen and the wall of the specimen box. In the quick freezing test, clean water should be injected into the specimen box, and the height of the water level should be 50mm higher than the specimen. When the temperature in the freeze-thaw chamber drops to -18℃, the timing starts. The freezing time in each freeze-thaw cycle is 4h. After the freezing is completed, water with a temperature of 19.0±1.0℃ is added immediately. The water adding time is within 10min, the water level is more than 20mm higher than the specimen, and the thawing time is 4h. After thawing, the freeze-thaw cycle is considered to be over and the next freeze-thaw cycle can be carried out.

[0100] The freeze-thaw test was stopped after 200 freeze-thaw cycles, the compressive strength of the specimens was tested, and the strength loss rate was calculated.

[0101] Strength loss rate = 1-compressive strength of the sample after 100 freeze-thaw cycles ÷ original compressive strength of the sample × 100%

[0102] like Figure 4 As shown, the freeze-thaw strength loss rate of the samples in Example 5 was the lowest, and the anti-freeze-thaw effect was the best, which was better than that in the comparative examples 1-3 (P<0.05).

[0103] The samples of Example 5, Comparative Example 1 and Comparative Example 2 after standard curing for 28 days were split by three-point bending using a press, and the crack width was controlled to be about 300-400 μm. Except for the area with a width of 1 cm on both sides of the crack, the surface of the sample was sealed with epoxy resin. Then, it was placed in an environment with a temperature of 25°C and a humidity of 75% RH for 8 weeks, and the crack width was tested on the 14th day, the 28th day and the 56th day, and the self-repair rate was calculated.

[0104] Self-repair rate = (initial crack width - crack width after standing for a certain period of time) ÷ initial crack width × 100%

[0105] like Figure 5As shown, the self-repair rate of the samples in Example 5 is the highest, which is better than that of the samples in Comparative Examples 1-2.

[0106] The applicant believes that the reason for the above results is that: the present invention adopts silane coupling agent, mesoporous silica and waste building materials for compound activation, and has good compatibility and lubricity with nano calcium carbonate and nano bentonite in combination with polyethylene wax, and can be evenly dispersed in paraffin; the fly ash is then activated with a silane coupling agent, and then grafted with polyacrylamide, which significantly enhances the adsorption and loading strength of the fly ash on alkaliphilic Bacillus, and further coats the premix b. The product is dispersed among the admixtures, which can not only effectively reduce the surface energy between particles and effectively reduce the agglomeration of particles, but also absorbs water and expands after the wall is broken, can closely fit the cracks to achieve filling and plugging, reacts with water, calcium hydroxide and other substances at the crack interface to repair the cracks, and at the same time, the alkaliphilic Bacillus further overflows after the wall is broken, and further repairs the cracks, thereby comprehensively improving the strength and durability of concrete, and achieving excellent repair effect. The present invention adopts mesoporous silica and waste building materials for compound grinding, which not only forms a large number of fine pores and a large specific surface area, but also the high silica content can effectively promote the formation of hydration products and effectively improve the void structure of concrete materials; the combination of fly ash and microsilica has good porosity, and when combined with prefabricated material c, it has excellent dispersion uniformity in the admixture, which not only effectively promotes the dispersion of structural stress, thereby producing an effective strengthening effect, but also can inhibit the generation and development of fine cracks, and has a significant structural stress compensation and anti-cracking effect.

[0107] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A green ultra-fine high-performance composite admixture, characterized in that: The raw materials include, by mass, 20-50 parts of fly ash, 15-25 parts of microsilica powder, 1.1-3 parts of silane coupling agent, 5-10 parts of mesoporous silica, 5-10 parts of waste building materials, 1-5 parts of nano calcium carbonate, 1-2 parts of nano bentonite, 1-3 parts of polyethylene wax, 10-20 parts of paraffin, 1-2 parts of fatty acid glyceride, 1-3 parts of calcium lactate, 1-4 parts of acrylamide, 0.01-0.1 parts of ammonium persulfate, 1-2 parts of alkaliphilic bacillus agent, 15-30 parts of limestone powder, 5-10 parts of urea, 1-6 parts of light-burned magnesium oxide expansion agent, 3-15 parts of quartz powder, 0.1-2 parts of redispersible latex powder and 0.1-0.5 parts of defoaming agent.

2. The green ultrafine high-performance composite admixture according to claim 1, characterized in that: Density of microsilica powder ≥550kg / m 3 , of which SiO2 and Al2O3 account for ≥95% by mass.

3. The green ultrafine high-performance composite admixture according to claim 1, characterized in that: The particle size of mesoporous silica is 100-500nm.

4. The green ultrafine high-performance composite admixture according to claim 1, characterized in that: The silane coupling agent is at least one of silane coupling agent KH570, silane coupling agent KH590 and silane coupling agent Si69.

5. The green ultrafine high-performance composite admixture according to claim 1, characterized in that: The content of live alkaliphilic Bacillus in the alkaliphilic Bacillus agent is 1-5×10 9 cfu / g.

6. The green ultrafine high-performance composite admixture according to claim 5, characterized in that: The alkaliphilic Bacillus is at least one of Bacillus sphaericus, Bacillus pasteurianus, Bacillus cohnii, Bacillus cereus and Bacillus licheniformis.

7. A method for preparing the green ultrafine high-performance composite admixture according to any one of claims 1 to 6, characterized in that: The steps include: S1. Mix fly ash and microsilica powder uniformly to obtain premix a; S2, grind the silane coupling agent, mesoporous silica and waste building materials for 10-20 min, add nano calcium carbonate, nano bentonite and polyethylene wax and continue grinding for 5-15 min, add paraffin, fatty acid glyceride and calcium lactate, stir at 70-80° C. to obtain premix b; S3, grind the silane coupling agent and fly ash, add deionized water and acrylamide, stir for 1-2h, add ammonium persulfate, stir at 70-80°C for 1-2h, cool to room temperature, add alkaliphilic bacillus agent, ultrasonically disperse for 1-4h, centrifuge, freeze-dry, crush and sieve, send into a drum, spray premix b on the surface, and freeze-dry to obtain premix c; S4. Mix limestone powder, urea, light-burned magnesium oxide expansion agent, quartz powder, redispersible latex powder and defoaming agent evenly, add premix a and premix c thereto and mix evenly.

8. The method for preparing the green ultrafine high-performance composite admixture according to claim 7, characterized in that: The mass ratio of the silane coupling agent used in S2 to the silane coupling agent used in S3 is 0.1-1:1-2.

9. The method for preparing the green ultrafine high-performance composite admixture according to claim 7, characterized in that: In S3, the ultrasound frequency is 5-12kHz.

10. Use of the green ultrafine high-performance composite admixture according to any one of claims 1 to 6 in preparing concrete.

Citation Information

Patent Citations

  • Micron-sized mineral admixture for concrete

    CN112174569A

  • Preparation method of concrete self-repairing microcapsule

    CN115073055A

  • Self-healing concrete and manufacturing method thereof

    CN116903308A